A peptoid interleukin‐15 receptor antagonist suppresses inflammation and arthritis in mice. Issue 11 (24th November 2022) - Cho, Kwang Bog; Shukla, Satya Prakash; Kannan, Maheshkumar; Zhang, Haowen; Amina, Sundus Jabeen; Zhou, Shuang; Chen, Yanping; Molligan, Jeremiah F; Taneja, Veena; Mohan, Chandra; Udugamasooriya, D Gomika; Guo, Bin
Abstract: Objective: To discover a novel peptoid antagonist that targets the interleukin‐15 (IL‐15) receptor and to evaluate its therapeutic efficacy in the treatment of inflammation and arthritis. Methods: A new compound (IFRA3, interleukin‐15 receptor antagonist 3) was discovered using a unique on‐bead two‐colour combinatorial cell screening of a peptoid library. The interaction of IFRA3 with IL‐15 receptor was assessed by in vitro pull‐down and thermal shift assays. The efficacy of IFRA3 in treating inflammation and arthritis was evaluated in mouse models. Results: IFRA3Q1 (a tetrameric derivative of IFRA3) inhibited the activity of IL‐15 and suppressed CTLL‐2 cell proliferation (which depends on IL‐15 activity). IFRA3Q1 exhibited strong in vivo anti‐inflammatory activity in carrageenan‐induced inflammation in mice. Furthermore, IFRA3Q1 inhibited collagen‐induced arthritis in DBA/1J mice. Conclusion: By binding to and inhibiting the function of IL‐15 receptor, IFRA3Q1 exhibited significant anti‐arthritis activity. Our findings suggest that IFRA3Q1 represents a new paradigm for arthritis therapy by targeting IL‐15 signalling. Abstract : IL‐15 plays an important role in rheumatoid arthritis and other autoimmune diseases. Using a combinatorial screening of a chemical library, we discovered a novel peptoid compound (IFRA3Q1) that binds to the IL‐15 receptor and blocks its function. Furthermore, IFRA3Q1 inhibits carrageenan‐induced inflammation and collagen‐induced arthritis in mice. These findings present an alternative strategy for blocking IL‐15, using peptoids instead of antibodies.